2011
DOI: 10.5089/9781463926540.006
|View full text |Cite
|
Sign up to set email alerts
|

Managing Capital Inflows: What Tools to Use?

Abstract: DISCLAIMER: This Staff DiscussionNote represents the views of the authors and does not necessarily represent IMF views or IMF policy. The views expressed herein should be attributed to the authors and not to the IMF, its Executive Board, or its management. Staff Discussion Notes are published to elicit comments and to further debate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
206
0
16

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(226 citation statements)
references
References 17 publications
4
206
0
16
Order By: Relevance
“…Inflows unrelated to country-specific economic fundamentals but instead driven by global driving forces, the argument goes, pose a threat to domestic financial stability. Curbing capital inflows by means of outright capital controls or other measures is often seen as the ultima ratio in a situation in which a country receives massive capital inflows driven by global determinants over which domestic policy has no control (see Ostry et al (2011) Pesaran CD-statistics are shown in parenthesis. * * * , * * , and * denote significance levels of 1%, 5% , and 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Inflows unrelated to country-specific economic fundamentals but instead driven by global driving forces, the argument goes, pose a threat to domestic financial stability. Curbing capital inflows by means of outright capital controls or other measures is often seen as the ultima ratio in a situation in which a country receives massive capital inflows driven by global determinants over which domestic policy has no control (see Ostry et al (2011) Pesaran CD-statistics are shown in parenthesis. * * * , * * , and * denote significance levels of 1%, 5% , and 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Even more important, national governments have to be willing to actively implement a rigorous macro-prudential framework, even at the risk of committing Type II errors that forestall sustainable expansions in credit growth. As emphasised by Ostry et al (2011) and Jeanne et al (2012), a broad macro-prudential framework can include a role for capital controls. Finally, excessive leverage in the non-financial sector (corporates and households) can be further deterred through tax and regulatory policies that do not favour debt financing over equity financing (see also Rogoff 1999).…”
Section: Financial Globalisation After the Crisis: Policy Reformsmentioning
confidence: 99%
“…He finds that foreign exchange policy objectives and overheating concerns have been the two main motives for capital controls, particularly since 2000. 3 See, for example, Ostry et al (2011), Klein (2012), Hutchison et al (2012), Patnaik and Shah (2012) and Warnock (2011). 4 NKI are measured as the difference between inflows by non-residents and net outflows by residents.…”
Section: Introductionmentioning
confidence: 99%